2011
DOI: 10.1111/j.1600-0447.2011.01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and clinical outcomes of bipolar disorder

Abstract: Daruy‐Filho L, Brietzke E, Lafer B, Grassi‐Oliveira R. Childhood maltreatment and clinical outcomes of bipolar disorder.Objective:  Adverse life events, especially early trauma, play a major role in the course and expression of bipolar disorder (BD). The aim of this article is to present a systematic review about the impact of childhood trauma on the clinical course of BD.Method:  A computer‐aided search was performed in Medline, ISI database, EMBASE, PsychInfo, Centre for Reviews and Dissemination, and Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
150
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(168 citation statements)
references
References 47 publications
11
150
2
5
Order By: Relevance
“…This study suggests the possibility that childhood abuse might increase soft bipolarity in the general adult population, which, in turn, might affect the pathogenesis or clinical outcomes of mood disorders. Several studies have reported that the history of childhood abuse is closely related to the onset, course, and treatment response of mood disorders (Alloy et al, 2006;Caspi et al, 2003;Daruy-Filho et al, 2011;Levitan et al, 1998;Nanni et al, 2012). The results of this study link childhood abuse to affective temperaments in aspects of depressive symptoms.…”
Section: Discussionsupporting
confidence: 50%
“…This study suggests the possibility that childhood abuse might increase soft bipolarity in the general adult population, which, in turn, might affect the pathogenesis or clinical outcomes of mood disorders. Several studies have reported that the history of childhood abuse is closely related to the onset, course, and treatment response of mood disorders (Alloy et al, 2006;Caspi et al, 2003;Daruy-Filho et al, 2011;Levitan et al, 1998;Nanni et al, 2012). The results of this study link childhood abuse to affective temperaments in aspects of depressive symptoms.…”
Section: Discussionsupporting
confidence: 50%
“…This may suggest that the presence of dissociation may have unfavorable effects on the course of the disease. Childhood abuse and neglect are the risk factors associated with worsening of clinical course in bipolar disorder (42). Childhood abuse was associated with suicidal ideation and suicide attempts in adults with bipolar disorder (43).…”
Section: Discussionmentioning
confidence: 96%
“…21,22 Childhood trauma also appears to impact the course of the illness, being associated with earlier illness onset, an increased number of comorbidities, and suicidal behavior. 20,23 Although childhood trauma is assumed to have an important role in the early expression of symptoms in BD, to the best of our knowledge, no studies that investigated the prodromal period of this disorder have systematically evaluated the presence of childhood trauma or its influence on the prodromal manifestations of BD.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, such as childhood trauma, may influence the expression of symptoms in BD, 20 as well as the prodromal features of the disorder. Patients with BD exhibit higher vulnerability to traumatic events during childhood.…”
Section: Introductionmentioning
confidence: 99%